PERAN KUALITAS LAYANAN DAN CUSTOMER EXPERIENCE DALAM MENINGKATKAN KEPUASAN MASYARAKAT - Ni Putu Kesya Krista Bela Pangky Swara; I Wayan Suartina; I Gede Aryana Mahayasa (Warmadewa Management and Business Journal (WMBJ), 2024)
This research was conducted with a purpose to determine the influence of service quality and customer experience on community satisfaction. This research took place at the Pandak Gede Village Office in Kediri District, Tabanan Regency. The population in this research is the people of Pandak Gede Village who have received services in 2022 as many as 2,675 people. The sample size determined was 96 respondents using simple random sampling technique. Data collection was carried out by conducting interviews and distributing questionnaires. Instrument testing was carried out using validity and reliability tests. The data analysis technique used is multiple linear regression. The results of the analysis prove that service quality and customer experience partially and simultaneously have a positive and significant effect on community satisfaction.